Inverted Polymer Solar Cells - Song Chen; Sai-Wing Tsang; Cephas E. Small; John R. Reynolds; Franky So (IEEE Photonics Journal)
Inverted bulk heterojunction polymer solar cells have become the preferred device architecture for roll-to-roll (R2R) processing, which allows large area devices to be fabricated on flexible substrates. Significant improvements in inverted solar cell performance have been made with novel photovoltaic polymers, along with optimized blend morphology and improved carrier extraction materials. For the first time, inverted polymer solar cells display their potential for low-cost R2R processing with power conversion efficiencies exceeding 8%.